The Linear and Nonlinear Electro-Mechanical Fin Actuator - Mahdi, Shaimaa A.; Abdul Redha, Zeina A. (Al-Khwarizmi Engineering Journal, 2018)
Electromechanical actuators are used in a wide variety of aerospace applications such as missiles, aircrafts and spy-fly etc. In this work a linear and nonlinear fin actuator mathematical model has been developed and its response is investigated by developing an algorithm for the system using MATLAB. The algorithm used to the linear model is the state space algorithm while the algorithm used to the nonlinear model is the discrete algorithm. The huge moment constant is varied from (-3000 to 3000) and the damping ratio is varied from (0.4 to 0.8).         The comparison between linear and nonlinear fin actuator response results shows that for linear model, the maximum overshoot is about 10%, rising time is 0.23 sec. and steady state occur at 0.51 sec., while For nonlinear model the maximum overshoot is about 5%, rising time is 0.26 sec. and steady state occurs at 2 sec.; i.e., the nonlinear fin actuator system gives faster and more accurate response than does the linear fin actuator system.